Noradrenergic influences in the basolateral amygdala on inhibitory avoidance memory are mediated by an action on α2-adrenoceptors. (January 2015) - Ferry, Barbara; Parrot, Sandrine; Marien, Marc; Lazarus, Christine; Cassel, Jean-Christophe; McGaugh, James L.
Highlights: Retrodialysis of idazoxan enhances amygdala norepinephrine release during inhibitory avoidance. Retrodialysis of UK 14, 304 decreases amygdala norepinephrine release during inhibitory avoidance. Idazoxan retrodialysis in the amygdala enhances inhibitory avoidance memory. Noradrenergic system in the amygdala influences inhibitory avoidance memory through pre-synaptic α2 -adrenoceptors. Summary: The role of norepinephrine (NE) in the consolidation of inhibitory avoidance learning (IA) in rats is known to involve α1 - and β-adrenoceptor systems in the basolateral nucleus of the amygdala (BLA). However, the amygdala also contains α2 -adrenoceptor subtypes, and local microinfusions of the selective α2 -adrenoceptor antagonist idazoxan and agonist UK 14, 304 respectively into the BLA enhance and inhibit IA performances when administered before acquisition. The present study investigated whether the effects of idazoxan and UK 14, 304 on IA were associated with changes in NE release within the BLA before and after one-trial inhibitory avoidance training. Male Sprague-Dawley rats were unilaterally implanted with a microdialysis probe in the BLA and were administered idazoxan (0.1 mM) or UK 14, 304 (10 μM) by retrodialysis infusion 15 min before the acquisition of IA. Dialysates were collected every 15 min for analysis of NE. Retrodialysis of idazoxan potentiated the release of NE induced by footshock application, whereas UK 14, 304 decreased NE release to the extent that the footshock failed to induce any measurable effect on NE levels. Idazoxan infusion enhanced IA retention tested 24 h later and this effect was directly related to the level of NE release in the BLA measured during IA acquisition. In contrast, the infusion of UK 14, 304 did not modify IA performances in comparison to control animals, possibly due to compensatory activity of the contralateral BLA. These results are consistent with previous evidence that amygdala NE is involved in modulating memory consolidation, and provide evidence for an involvement of presynaptic α2 -autoceptors in the BLA in this process.